ORGANIC ARCHITECTURE APPROACH IN SURABAYA ZOO PLANNING - Hadiwibawa, Airlangga Cahya; Mutiara, Elok; Mappaturi, Andi Baso (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green TechnologyDO - 10.18860/icgt.v10i0.1170, 2020)
Surabaya zoo roommates are wildlife conservation that has been overshadowed by retaining a long time. At this time it is the declining environmental quality of the region. This decline Affects the animal's death. It takes a proper design to restore the environmental conditions of the Surabaya Zoo. Through the organic architectural approach can be seen Several principles related to environmental regulation. Ie by way of responding to the climatic conditions of the object design environment. The goal is to create a space that is comfortable and healthy, especially for animals. Animals are placed far from their natural habitat in the zoo. This condition requires setting cage space roommates do away with its natural condition. for the needs of animals into a settlement measuring point problem. Determination of organic architecture can approach Become a place to organize all the facilities and infrastructure needs Surabaya zoo Becomes more comfortable and healthy. Showed a concept that synergizes adaptable animals and plants, water distribution, HVAC related to wind and solar circulating. Overall closely related to the optimization of natural resources.